Implementasi Framework Reactjs Pada Desain Aplikasi E-menu Restoran Dengan Payment Gateway (Studi Kasus: Restoran Hosit Bangka Kuliner) - Diah Aryani; Willi Kornellius; Yulhendri Yulhendri; Hani Dewi Ariessanti (UNIVERSITAS RAHARJA, 2024)
Sustaining and enhancing customer satisfaction consistently is a crucial determinant for a company to achieve competitive advantage in its industry, E-Menu is an innovative application that functions as a replacement for conventional menus and ordering systems. Therefore, continuous innovation is needed to improve service quality by implementing e-menus which are expected to shorten service time and improve service quality to customers. The Hosit Bangka Kuliner restaurant, which still uses conventional methods in terms of service and operational aspects in the process of ordering food or drinks, also does not have a checkout menu, so the waiter must read the menu list of the selected orders to confirm the order, which is less effective. This study aims to develop an e-menu application that displays different functionalities categorized according to the intended user, namely (employees and customers to display menu details and order status, in addition to functioning as a menu ordering tool.The prototype method is utilised as the research methodology for the development of an E-Menu website. The utilised programming languages comprise HTML, CSS, and ReactJs. The expected results from the development of this application are none other than to serve as a viable solution to address current problems, and to increase customer satisfaction by providing an optimal user experience.